007. Distal Ileal Atresia and Total Colon Agenesis with Anorectal Malformation: A Case Report - Pramudita, Nyoman; Darmajaya, I Made (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical Education, 2024)
Background : Atresia of the distal ileum and colon agenesis are rare conditions and can be the cause of obstructive symptoms. Case : A 1 day old baby girl complained of no anus since birth. The patient has no bowel movements or vomiting. The patient's stomach appears increasingly bloated. On physical examination of the abdomen revealed distension accompanied by difficult to hear bowel sounds. There was no anus or fistula in the patient but there is a dimple in the anus. Another abnormality found in the patient was the presence of CTEV on both of the patient's legs. The patient was planned for exploratory laparotomy and colostomy surgery. the length of the jejunum and ileum proximal to the ligament of Treitz was found to be 50 cm. The distal ileum, caecum, colon, rectum and anus were not found. An ileostomy was performed on this patient. The patient died 13 hours after surgery. Conclusion: Total colonic agenesis is a rare case and usually occurs with other congenital abnormalities. Early diagnosis and appropriate initial treatment are very important in this case. colonic agenesis causes congenital short bowel (CSB). CSB causes malabsorption due to inadequate intestinal length, which interferes with absorption. Staged surgery is a good option in the management of total colonic agenesis.